Spatial Perception of Urban Island under the Influence of Gentrification: A Case Study of Jiangxinzhou, Nanjing - Zou, Jiayun (International Journal of Natural Resources and Environmental Studies, 2026)
With the acceleration of urbanization, urban islands are undergoing a spatial transformation from ecological conservation areas to new growth poles for urban development. In this process, gentrification plays a crucial role, profoundly reshaping both the physical and social spaces of these islands. Taking Jiangxinzhou in Nanjing as a case study, this paper employs a combination of field surveys and online textual analysis to explore the characteristics of spatial perception of urban islands under the influence of gentrification. The results indicate that Jiangxinzhou has experienced significant changes in ecological environment, road transportation, architectural style, public amenities, and cultural and recreational spaces. Overall, public sentiment toward these five categories of space is positive, with the highest satisfaction observed in public spaces, while cultural spaces exhibit the highest proportion of negative perceptions. During the development process, urban islands face several challenges, including conflicts between ecological preservation and aesthetic pursuits, lack of diversity in public transportation, monotonous building functions, insufficient public spaces, and the erosion of local culture. Based on these findings, this study proposes corresponding optimization strategies, aiming to provide references for the planning and development of urban islands in the context of gentrification.